Identification of novel therapeutic targets to modulate proteostasis in humans - Pereira, Marisa de Almeida (2023)
Transfer RNAs (tRNAs) are a class of small non-coding RNA molecules essential for mRNA translation and cellular homeostasis. After transcription, tRNAs undergo various chemical modifications, catalyzed by different classes of tRNA modifying enzymes. These modifications have a profound impact on the structure, stability, and accurate decoding of mRNA sequences by tRNAs. In addition, they also influence the generation of tRNA-derived small RNAs, known as tsRNAs, adding an extra layer of complexity to the regulatory functions of tRNAs. Dysregulation of tRNA modifications can lead to increased missense errors, impaired codon decoding, and protein aggregation, contributing to cellular dysfunction. Growing evidence suggests a link between tRNA hypomodification, abnormal expression of tRNA modifying enzymes, and protein conformational diseases, including neurodegenerative and metabolic disorders. However, the precise mechanisms underlying the relationship between tRNA modifications levels and proteostasis imbalance are not fully understood. This study hypothesizes that the dysregulation of tRNA modifying enzymes affects translation efficiency, promoting protein aggregation, and activation of the cellular integrated stress response, particularly when it leads to tRNA hypomodification. Therefore, the main aim of this thesis was to investigate the impact of tRNA modifying enzymes on protein aggregation and its implications for human health. In this study, the critical role of wobble uridine tRNA modifying enzymes in maintaining the delicate balance between protein synthesis and degradation in different human cell lines was demonstrated. Furthermore, this research highlighted the relevance of ELP3 and its associated tRNA modifications in preserving proteostasis in amyloid-based models of Alzheimer's disease. This emphasizes the potential of tRNA modification modulation as a therapeutic approach for neurodegenerative disorders. Additionally, the influence of TRMT2A expression on the generation of tsRNAs was demonstrated, shedding light on its role in regulating the production of these molecules and its impact on cellular homeostasis. Overall, this thesis provides valuable insights into the critical functions of tRNA modifying enzymes and their involvement in proteostasis maintenance, with potential implications for the development of novel therapeutic strategies for protein conformational diseases.